2015
DOI: 10.4236/ajac.2015.65043
|View full text |Cite
|
Sign up to set email alerts
|

HPLC Method Development and Validation of S(-)-Carvedilol from API and Formulations

Abstract: A simple chiral HPLC method was developed and validated for quantification of S(-)-Carvedilol in Active Pharmaceutical Ingredient (API) and marketed tablet formulation of racemic Carvedilol. Chiral resolution of enantiomers of Carvedilol was achieved on Phenomenex Lux-cellulose-4 (250 mm × 4.6 mm; 5 µ particle size) chiral column by using a mobile phase, Isopropanol and n-Heptane (60:40 v/v), at a flow rate of 1.0 ml/min and by employing UV detection at 254 nm wavelength. The method was validated according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In this study the enantioselective resolution was confirmed by estimating the enantiomeric purity of the product by using an earlier reported chiral HPLC method [33]. The racemic Carvedilol was analyzed by the chiral HPLC method and retention time of the ( R )-(+)- and ( S )-(−)-enantiomers were found as 7.389 and 9.399 min, respectively (Fig.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…In this study the enantioselective resolution was confirmed by estimating the enantiomeric purity of the product by using an earlier reported chiral HPLC method [33]. The racemic Carvedilol was analyzed by the chiral HPLC method and retention time of the ( R )-(+)- and ( S )-(−)-enantiomers were found as 7.389 and 9.399 min, respectively (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…The samples prepared after extraction were analyzed by an earlier reported chiral HPLC method for the enantioselective resolution of racemic Carvedilol [33]. Accordingly, the stationary phase used was Phenomenex Lux Cellulose-4 column (250 × 4.6 mm; 5 µ particle size).…”
Section: Methodsmentioning
confidence: 99%
“…The development of novel pharmaceutical formulations not only demands the finding of the optimal combination of active ingredients, but it may also require specific analytical methodologies suitable for determination of the multiple drugs that are present in the formulation. Some of the most used Active Pharmaceutical Ingredients (API) in the development of formulations for combination therapy for the treatment of metabolic syndrome are: bezafibrate (BZT, pK a = 3.6), a representative fibrate widely used in the treatment of hypercholesterolemia [6,7]; gliclazide (GZD, pK a = 5.8), an oral hypoglycemic agent, belonging to second-generation sulphonylureas, which is used in type II diabetes (noninsulin-dependent diabetes mellitus) [8][9][10]; glimepiride (GMP, pK a = 6.2), an oral bloodglucose-lowering drug of the third-generation sulfonylureas, used for the treatment of diabetes [11][12][13]; telmisartan (TEL, pK a = 4.5), a synthetic analog of angiotensin II receptor blocker used in the management of hypertension [14][15][16]; and carvedilol (CVD, pK a = 7.5), a non-selective beta-alpha blocker 1, used in the treatment of high blood pressure [17][18][19]. Since all these compounds contain aromatic rings in their structure (see Figure 1), they cannot be simultaneously quantified following a UV−Vis spectrophotometric analytical method since all of them absorb in the same region of the UV-spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, a rapid HPLC-DAD methodology was developed for simultaneous quantification of bezafibrate (hypercholesterolemia), gliclazide and glimepiride (di- Different HPLC chromatographic methods have been reported for individual determination of BZT [20][21][22], GZD [8,9,23], GMP [11,12,24], TEL [14,15,25], and CVD [17,18]. However, fast methodologies for the quantification of more than two drugs in a single run are limited.…”
Section: Introductionmentioning
confidence: 99%